An Effective Protocol for Micropropagation of Edible Bamboo Species (Bambusa tulda and Melocanna baccifera) through Nodal Culture - Sayanika Devi Waikhom; Bengyella Louis (The Scientific World Journal)
High demand for edible bamboo shoots of Bambusa tulda and Melocanna baccifera in many Asian ethnic groups has led to the need for developing intensive bamboo farming. To achieve this, in vitro regeneration of bamboo plantlets is needed due to the long and irregular bamboo flowering cycle and scarcity of bamboo seeds. An effective protocol for plantlets regeneration in B. tulda and M. baccifera from nodal explants following validation of the species using the sequence of trnL-F intergenic spacer region is described. Effective axillary bud breaking was achieved at 3 mg/L of 6-benzylaminopurine (BAP) in MS medium. Importantly, combining 2 mg/L of kinetin (Kn) with 3 mg/L of BAP produced a synergistic effect for shoot multiplication in B. tulda and M. baccifera. Under optimized conditions in half-strength MS medium supplemented with 3 mg/L of indole-3-butyric acid (IBA), 10 mg/L of coumarin, and 3% sucrose, profuse production of dark-brown rhizome in B. tulda and abundant rooting (81.67%, P<0.05, F=15.46) for M. baccifera within 30 days were achieved. The established protocol and the validation of the reported species at the molecular level will be of help to stakeholders in edible bamboo trade to conserve gene-pool and increase productivity.